Faktor penentu indeks pembangunan manusia dan hubungannya dengan belanja infrastruktur serta pertumbuhan ekonomi Kabupaten/Kota Provinsi Jambi - Herinoto, Herinoto; Rachmad R, M.; Zulfanetti, Zulfanetti (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to analyze the factors that determine the Human Development Index (HDI), to analyze the relationship between HDI and infrastructure spending, and to analyze the relationship between infrastructure spending and economic growth in districts/cities in Jambi Province. The data used in this study are secondary data with the type of Time Series 2012-2018 and Cross Section 11 districts/cities. This study uses Panel Data Multiple Regression Analysis and Simple Correlation Analysis using the E-views 10 tool. The results of this study indicate that the HDI of districts/cities in Jambi Province increases every year, partially the ratio of teachers to students, number of health facilities, and density. The population has a positive and significant effect in determining HDI. While the poverty factor has a negative but not statistically significant effect in determining the HDI of districts/cities in Jambi Province with an R-Square value of 0.9312. The relationship between HDI and infrastructure spending has a negative and insignificant effect, which means that an increase in infrastructure spending will increase the decrease in the value of HDI. The relationship between growth spending and economic growth has a positive and significant effect, which means that an increase in the value of infrastructure spending will increase the value of economic growth. Â